Transkingdom Interactions Important for the Pathogenesis of Human Viruses. (17th December 2020) - Nishimoto, Andrew; Wohlgemuth, Nicholas; Rosch, Jason; Schultz-Cherry, Stacey; Cortez, Valerie; Rowe, Hannah M
Abstract: The bacterial, fungal, and helminthic species that comprise the microbiome of the mammalian host have profound effects on health and disease. Pathogenic viruses must contend with the microbiome during infection and likely have evolved to exploit or evade the microbiome. Both direct interactions between the virions and the microbiota and immunomodulation and tissue remodeling caused by the microbiome alter viral pathogenesis in either host- or virus-beneficial ways. Recent insights from in vitro and murine models of viral pathogenesis have highlighted synergistic and antagonistic, direct and indirect interactions between the microbiome and pathogenic viruses. This review will focus on the transkingdom interactions between human gastrointestinal and respiratory viruses and the constituent microbiome of those tissues.